2015
DOI: 10.1371/journal.pone.0133466
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Heart Failure: A Comparison of Clinical Presentation and Outcome between Hypertensive Heart Failure of Pregnancy and Idiopathic Peripartum Cardiomyopathy

Abstract: AimsThere is controversy regarding the inclusion of patients with hypertension among cases of peripartum cardiomyopathy (PPCM), as the practice has contributed significantly to the discrepancy in reported characteristics of PPCM. We sought to determine whether hypertensive heart failure of pregnancy (HHFP) (i.e., peripartum cardiac failure associated with any form of hypertension) and PPCM have similar or different clinical features and outcome.Methods and ResultsWe compared the time of onset of symptoms, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 50 publications
5
80
0
2
Order By: Relevance
“…On the other hand, a recent single-center study of 30 patients in Cape Town, South Africa, reported 5 deaths (17%) in a mean follow-up duration of 3.5 years 34 (accounting for the majority of deaths in a larger cohort of 152 patients presenting with cardiovascular disease in pregnancy 86 ). In a larger study of 176 patients in Soweto, South Africa, 13% died and 25% had persistent LVEF <35% at 6 months.…”
Section: Racial and Geographic Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, a recent single-center study of 30 patients in Cape Town, South Africa, reported 5 deaths (17%) in a mean follow-up duration of 3.5 years 34 (accounting for the majority of deaths in a larger cohort of 152 patients presenting with cardiovascular disease in pregnancy 86 ). In a larger study of 176 patients in Soweto, South Africa, 13% died and 25% had persistent LVEF <35% at 6 months.…”
Section: Racial and Geographic Differencesmentioning
confidence: 98%
“…A recent report directly compared 30 cases of PPCM with 53 cases of hypertension-associated heart failure in pregnancy in a single referral center in South Africa and found that hypertension-associated heart failure typically presented before delivery, was associated with cardiac hypertrophy and preserved EF, and had a better prognosis. 34 Even in the absence of clinical heart failure, a number of echocardiographic studies have shown that preeclampsia causes diastolic dysfunction, measured by various parameters, including E/E', myocardial performance index, and myocardial strain. [35][36][37] The diastolic dysfunction is in part independent from blood pressure elevations and can persist up to 1 year after delivery and resolution of preeclampsia.…”
Section: Preeclampsia and Hypertensionmentioning
confidence: 99%
“…Since there is an overlap of presenting features between PPCM and other hypertensive pathologies such as preeclampsia [14,17,18] such as shortness of breath, fatigue and swelling [8] it is important to be mindful of PPCM and how to diagnose it. Transthoracic echocardiography enables differentiation of heart failure with preserved ejection fraction, commonly observed in women with preeclampsia, from that with peripartum cardiomyopathy in which a reduced ejection fraction is more common.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, the incidence, contributing comorbidities (e.g., hypertension and pre-eclampsia), and outcome seem to be variable, depending on the geographical region, ethnic background, and the inclusion criteria of the given study. 5, 6 It was recently suggested that PPCM may be associated with increased placental production of soluble fms-like tyrosine kinase-1 (sFlt-1), as in pre-eclampsia, for which it has long been thought to be associated. 7 The antiangiogenic factor sFlt-1 reduces free circulating concentrations of the angiogenic factors placenta growth factor (PlGF) and vascular endothelial growth factor (VEGF) and blunts the beneficial effects of these angiogenic factors on the maternal endothelium.…”
Section: Biomarker Testingmentioning
confidence: 99%
“…6 Clinical assessment, echocardiography, and blood analysis for PPCM patients were performed at the time of admission and hospitalization. Plasma samples were also collected from healthy non-pregnant women (n=29), healthy pregnant women (n=10; 20-36 weeks gestation), and healthy women after delivery (within 24 h of delivery; n=30).…”
mentioning
confidence: 99%